ANALISIS PENGARUH KUALITAS PRODUK DAN PELAYANAN TERHADAP KEPUASAN KONSUMEN DENGAN HARGA SEBAGAI VARIABEL MODERASI - Rahayu Triastity, Diana Hendrawati, Marjam Desma Rahadhini & (Universitas Slamet Riyadi, 2017)
The purpose of this study was to analyze the significance of the influence ofproduct quality, service quality and price to customer satisfaction and to analyze theeffect of product quality and service quality to customer satisfaction with price as amoderating variable. This research is a survey on consumer Omah WedanganMojosongo Surakarta. Sample of 100 people with accidental sampling technique. Datacollection technique used questionnaire and literature. Data were analyzed usedmultiple linear regression and test of absolute difference. The results showed that thequality of products, service quality and price have a significant effect on customersatisfaction. Price does not moderate the effect of product quality and service quality tocustomer satisfaction. Results of determination coefficient of 0,450 means that the effectof variable quality products, services and prices of consumer satisfaction is equal to45,0%, while the remaining 55,0% is influenced by other variables not examined, forexample, is the location of the business and promotion.Keywords: product quality, servicy quality, price, customer satisfaction